Punishment, support, or discipline? Taking stock of recent debates about homeless governance in neoliberal cities. Issue 8 (25th June 2021) - Grainger, Garrett L.
Abstract: An interdisciplinary debate emerged in the 1990s about the nature of homeless governance in neoliberal cities. Contributions to this discussion have interrogated the form, function, and legitimacy of contemporary homeless management. Urban scholars have differentiated three techniques of homeless governance: punishment, support, and discipline. A subset of scholarship has defined punitive governance as an illegitimate act of repression that promotes urban revitalization by excluding the homeless from urban political economies, supportive governance as a legitimate act of voluntary or coercive care that helps the homeless survive a traumatic life experience, and disciplinary governance as an illegitimate act of production that fortifies urban political economies by including rather than excluding homeless individuals into bourgeois institutions. An emerging body of research demonstrates frontline workers coordinate these techniques of governance to pursue the aims of institutional elites. This article outlines the main points of contention in this debate, examines significant empirical findings that scholars have reported, and identifies salient knowledge gaps to be addressed in future research.